Study of Body Image among Female Adolescent Students based on Personality - et. al., Dr. G. K. Dhokrat, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The body image of female adolescents was analysed in this study based on their personality characteristics. This study was carried out on 50 female adolescent students from Navi Mumbai Maharashtra. The average age of selected female adolescent students was 14.92 years. Eysenck's PEN inventory was used to assess psychoticism, extraversion and neuroticism dimensions of personality. To assess body image of the selected subjects, Modified Version of Self-Assessment Questionnaire for Body Image, prepared by Agashe and Karkare (2008) was preferred. The stepwise regression was used to analyse the data. The results indicate that psychoticism, extraversion and neuroticism was strongly associated with the body image of female adolescent students. The regression model prediction reveals that psychoticism, extraversion and neuroticism were able to generate 54.7% variance on body image of female adolescent students. It was concluded that personality dimensions viz. psychoticism, extraversion and neuroticism are very strong predictors of body image in female adolescent students